Method for Assessing the Impact of Creating a New Industrial Infrastructure on the Industrial and Socio-Economic Development of Regions - T. A. Burtseva; A. R. Akhmadov (Ekonomika Nauki, 2022)
The article presents the results of a study that substantiates the effectiveness of creating new industrial enterprises based on clusters, industrial parks and technology parks in the regions of Russia for their development. The authors proposed a method that allows using authoritative national ratings and the author’s rating of the regional new industrial infrastructure to quantify the impact of the creation of new industrial enterprises in the region on the socio-economic situation of the regions and their environmental situation. The advantages of the method include its reliability and objectivity, information security. As a result, the conclusions are substantiated: the created technology parks, clusters and industrial parks play a significant role for the development of the industry of the regions, improving the environmental situation and accelerating socio-economic development, but the process of creating industrial enterprises using a new industrial infrastructure requires intensification. The results obtained will contribute to solving the problem of measuring the effectiveness of the development and functioning of regional industrial systems.